The second order multi-valued boundary value problem and impulsive neutral functional differential inclusions in Banach spaces - Wei, L.; Zhu, Jiang (Нелінійні коливання, 2008)
In this paper, by using the new fixed point theorem of O’Regan and Precup and noncompact measure, the existence of solutions of second order multivalued boundary-value problem in Banach spaces and the existence of a mild solution for impulsive neutral functional differential inclusions in Banach spaces are studied. The compactuess conditions and the upper semicontinuity conditions of multivalued integral operators are weaken in this paper.